Sour Cherries but Not Apples Added to the Regular Diet Decrease Resting and fMLP-Stimulated Chemiluminescence of Fasting Whole Blood in Healthy Subjects - Bialasiewicz, Piotr; Prymont-Przyminska, Anna; Zwolinska, Anna; Sarniak, Agata; Wlodarczyk, Anna; Krol, Maciej; Markowski, Jaroslaw; Rutkowski, Krzysztof P; Nowak, Dariusz (Journal of the American College of Nutrition, 2018)
Berry fruits rich in anthocyanins have antioxidant and anti-inflammatory properties. Blood phagocytes are an important source of oxidants that contribute to inflammatory response and oxidative stress. We examined the effect of sour cherry consumption on luminol-enhanced whole blood chemiluminescence (LBCL) reflecting oxidants generation by circulating phagocytes in healthy subjects. Thirty-four and 29 healthy subjects (on a regular diet) consumed 500 g of sour cherries containing 346.5 mg of total anthocyanins or 500 g of anthocyanin-free apples everyday (between 1100 and 1400 hours) for 30 days. Twenty-four volunteers without any dietary intervention served as the control with respect to LBCL changes over the study period. Fasting blood and spot morning urine samples were collected before and after the fruit courses and after the 10-day wash-out period to measure resting and agonist (fMLP)-induced LBCL, blood cell count, concentration of various phenolics, and plasma antioxidant activity. Sour cherries inhibited (p < 0.05) median resting LBCL (by 29.5% and 33.7%) and fMLP-LBCL (by 24.7% and 32.3%) after 30-day consumption and after 10-day wash-out, respectively. No changes in LBCL were noted in the apple consumers and controls. Increased urinary levels of chlorogenic, 4-hydroxyhippuric, and 3-hydroxyhippuric acids occasionally correlated negatively with resting and fMLP-LBCL in sour cherry consumers. Other measured variables did not change in all groups over the study period. The inhibition of resting and agonist-induced LBCL suggests that regular sour cherry consumption may suppress the formation of reactive oxygen species by circulating phagocytes and decrease the risk of systemic imbalance between oxidants and antioxidants. This may be attributed to the anthocyanins in sour cherry and be one of mechanisms of the health-promoting effects of consumption of anthocyanin-rich fruits.